ON THE HISTORICAL-ETYMOLOGICAL FEATURES OF SOME THEONYMS IN THE UZBEK LANGUAGE - Rakhimova Norjongul Mahsud kizi (Modern American Journals, 2025)
This article investigates the linguistic origins of theonyms (Tangri, Xudo, Parvardigor) as essential components of religious lexicon in the Uzbek language, along with their cultural and spiritual significance. The study analyzes the historical evolution and contemporary usage of these onomastic units, which have developed under the influence of various languages, employing scientific linguistic methodologies.
Keywords: Theonym, theonymy, Tangri, Parvardigor, Khudo.